PG107 Mass simulation: delivering mass scale simulation at the 02 Arena. (10th November 2020) - Collins, Tim; Laws-Chapman, Colette; Houslip, Louise
Abstract : Introduction: NHS Nightingale London provided a critical care environment for creating capacity within the healthcare system. An education faculty designed & delivered a curriculum with the aim of equipping the workforce with the skills to work within NHS Nightingale at the Excel. NHS Nightingale presented unique challenges, including unfamiliar working practices, equipment & team membership variables, whilst working in a large and noisy environment, originally built as an exhibition centre 1. Simulation is an education modality that is employed to produce a safe experience to help prepare learners for a future real event 2. A 12 bed high-fidelity simulation facility was set up in The O2 Arena to replicate clinical reality for what will be anticipated within NHS Nightingale. Providing mass scale simulation in an arena provided many complexities which were confounded by the emergent situation of having to rapidly increase ICU provision due to COVID-19 pandemic. Methods: A simulation ward was built on the arena floor, aiming to provide clinical simulation for staff working at NHS Nightingale. We had 5 days to design and implement a simulation curriculum with limited kit availability. The large and acoustically challenging arena with no privacy, as well as social distancing, made it difficult to communicate and facilitate debriefs. Due to NHS surge plans already being activated, there was limited adult critical care educators, which created variability with the faculties expertise in simulation and critical care. There was variance in the learners which included both experienced & non-experienced critical care staff, through too volunteers with no health care background. Results: In total 2732 learners went through the education curriculum which involved a large component of simulation education. The curriculum was positively evaluated by learners. Discussion: The faculty adopted a co-facilitation, adaptive approach to support simulation and debriefing. Daily pre-briefing and debriefing allowed iterative adaptation of the programme and supported faculty development. Social distancing was maintained by limiting participants per scenario, providing short simulation sessions and distancing during debrief. The plus/delta debrief model was used as this provides a swift debrief whilst also allowing novice and experts to debrief to successful outcomes 3. Scenarios with differentiated learning outcomes were matched to the streamed groups depending on their expertise and where applicable benchmarked to national competencies 4. Conclusion: A large and skilled faculty, creative and adaptive to varying learner needs using a rapid improvement framework ensured that large scale simulation could be implemented within an arena. Reference: Collins T, Laws-Chapman C & Houslip L ( 2020) Reflection on NHS Nightingale London. Resuscitation Today. 7:10–12. https://www.resustoday.com/view-latest-issue/ Gaba D ( 2004) The future vision of simulation in health care. Qual Saf Health Care 13:i2–10. Schertzer K, Patti L. In Situ Debriefing in Medical Simulation. [Updated 2019 Oct 22]. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; [Accessed 06/06/2020] Critical Care Network National Nurse Leads (CC3N) (2015) 'National Competency Framework for Registered Nurses in Adult Critical Care . Step 1 competencies'.